Patient's Family Perception of Service Satisfaction Nursing Care in the Covid-19 Era in the Children's Room Indramayu Hospital in 2021 - Winani, Winani; Efendi, Bachtiar; Aziz, Rofan (Universitas Pendidikan Indonesia, 2021)
Satisfaction of the patient's family with nursing care in the hospital is very important in providing an overall picture of the quality of health services, especially in the children's room. This study aims to determine the Patient's Family Perception of the Satisfaction of Nursing Care Services in the Covid-19 Era in the Children's Room of the Indramayu Hospital. This research is a quantitative research using descriptive method. The population in the study amounted to 265, with a sample of 100 respondents. The results of the study illustrate that 10% of respondents are satisfied with the Nursing Care Service, 7% are satisfied based on the reliability dimension, 21% are satisfied based on the responsiveness dimension, 8% are satisfied based on the assurance dimension, 67% are satisfied based on the empathy dimension, and 39% are satisfied based on the tangible dimension. The results of these studies have not reached the standard according to the Decree of the Minister of Health Number 129/Menkes/SK/II/2008 concerning Minimum Service Standards for Hospitals. For this reason, hospitals can carry out regular evaluations to find out what must be improved and maintained in the services provided so that hospitals can achieve better quality standards by making continuous quality improvements every three months with one month of data collection.